2002
DOI: 10.1111/j.1469-8749.2002.tb00266.x
|View full text |Cite
|
Sign up to set email alerts
|

Fluoxetine response in children with autistic spectrum disorders: correlation with familial major affective disorder and intellectual achievement

Abstract: One hundred and twenty‐nine children, 2 to 8 years old, with idiopathic autistic spectrum disorder diagnosed by standard instruments (Childhood Austim Ratings Scale and Autism Diagnostic Observation Schedule) were treated with fluoxetine (0.15 to 0.5mg/kg) for 5 to 76 months (mean 32 to 36 months), with discontinuation trials. Response criteria are described. Family histories were obtained using the family history method in repeated interviews. Fluoxetine response, family history of major affective disorder, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(19 citation statements)
references
References 33 publications
(35 reference statements)
2
17
0
Order By: Relevance
“…Although there were no significant side effects, there also were no significant improvements in measures of speech or social interaction. Delong et al (2002) reported a 69% positive response rate for fluoxetine in children, aged 2-8, who were autistic. Treatment parameters were quite variable with treatment duration ranging from 5 to 76 months and doses ranging from 4 to 40 mg/day.…”
Section: Pharmacological Treatmentsmentioning
confidence: 97%
“…Although there were no significant side effects, there also were no significant improvements in measures of speech or social interaction. Delong et al (2002) reported a 69% positive response rate for fluoxetine in children, aged 2-8, who were autistic. Treatment parameters were quite variable with treatment duration ranging from 5 to 76 months and doses ranging from 4 to 40 mg/day.…”
Section: Pharmacological Treatmentsmentioning
confidence: 97%
“…It has been suggested that selective serotonin reuptake inhibitors (SSRIs) may be useful in the treatment of certain symptoms of subjects with ASDs (Posey, Erickson, Stigler, & McDougle, 2006) including repetitive behaviors (Hollander et al, 2005; McDougle, Epperson, Price, & Gelernter, 1998; McDougle et al, 1996), anxiety (Buchsbaum et al, 2001), irritability (Owley et al, 2005), aggression and self-injurious behavior (Hellings, Kelley, Gabrielli, Kilgore, & Shah, 1996), and more global behavior (Cook, Rowlett, Jaselskis, & Leventhal, 1992; DeLong, Ritch, & Burch, 2002; Namerow, Thomas, Bostic, Prince, & Monuteaux, 2003; Sugie et al, 2005). However, a recent large controlled trial study by King and colleagues (2009) did not find a reduction in repetitive behaviors by citalopram.…”
Section: Introductionmentioning
confidence: 99%
“…A recently published meta-analysis does not support the use of SSRIs in autism (Williams et al, 2013). However, positive effects of fluoxetine on core autistic symptoms have been shown in individual cases and subgroups of autistic children and in adults with ASD (DeLong et al, 1998, 2002; Makkonen et al, 2011; Hollander et al, 2012). Anxiety and obsessive–compulsive symptoms which associate with autism can be ameliorated by fluoxetine in adult ASD (Buchsbaum et al, 2001; Hollander et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Although some studies suggest that fluoxetine may be beneficial for core features of ASD in adults (Williams et al, 2013) and in individual cases and subgroups of children with autism (DeLong et al, 1998, 2002; Hollander et al, 2012), a recent meta-analysis indicates that there is not enough evidence to support the use of SSRIs in autism (Williams et al, 2013). In addition, the possible side-effects of the drug treatment are a main concern in clinics.…”
Section: Introductionmentioning
confidence: 99%